Paediatric in-hospital cardiac arrest: Factors associated with survival and neurobehavioural outcome one year later. (March 2018) - Meert, Kathleen; Telford, Russell; Holubkov, Richard; Slomine, Beth S.; Christensen, James R.; Berger, John; Ofori-Amanfo, George; Newth, Christopher J.L.; Dean, J. Michael; Moler, Frank W.
Abstract: Objective: To investigate clinical characteristics associated with 12-month survival and neurobehavioural function among children recruited to the Therapeutic Hypothermia after Paediatric Cardiac Arrest In-Hospital trial. Methods: Children (n = 329) with in-hospital cardiac arrest who received chest compressions for ≥2 min, were comatose, and required mechanical ventilation after return of circulation were included. Neurobehavioural function was assessed using the Vineland Adaptive Behaviour Scales, second edition (VABS-II) at baseline (reflecting pre-arrest status) and 12 months post-arrest. Norms for VABS-II are 100 (mean) ±15 (SD). Higher scores indicate better functioning. Outcomes included 12-month survival, 12-month survival with VABS-II decreased by ≤15 points from baseline, and 12-month survival with VABS-II ≥70. Results: Asystole as the initial arrest rhythm, administration of >4 adrenaline doses, and higher post-arrest blood lactate concentration were independently associated with lower 12-month survival; an adrenaline dosing interval of 3–<5 min and open chest compressions were independently associated with greater 12-month survival. Use of extracorporeal membrane oxygenation (ECMO) and higher blood lactate were independently associated with lower 12-month survival with VABS-II decreased by ≤15 points from baseline; open chest compressions was independently associated with greater 12-month survival with VABS-II decreased by ≤15 points. Asystole as the initial rhythm, use of ECMO, and higher blood lactate were independently associated with lower 12-month survival with VABS-II ≥70; open chest compressions was independently associated with greater 12-month survival with VABS-II ≥70. Conclusions: Cardiac arrest and resuscitation factors are associated with long-term survival and neurobehavioural function among children who are comatose after in-hospital arrest.